Site-Specific Glycosylation of Recombinant Viral Glycoproteins Produced in Nicotiana benthamiana - Margolin, Emmanuel; Allen, Joel D.; Verbeek, Matthew; van Diepen, Michiel; Ximba, Phindile; Chapman, Rosamund; Meyers, Ann; Williamson, Anna-Lise; Crispin, Max; Rybicki, Edward (Frontiers in Plant Science, 2021)
There is an urgent need to establish large scale biopharmaceutical manufacturing capacity in Africa where the infrastructure for biologics production is severely limited. Molecular farming – producing pharmaceuticals in plants - offers a cheaper alternative to mainstream expression platforms, and is amenable to rapid large-scale production. However, there are several differences along the plant protein secretory pathway compared to mammalian systems, which constrain the production of complex pharmaceuticals. Viral envelope glycoproteins are important targets for immunization, yet in some cases they accumulate poorly in plants and may not be properly processed. Whilst the co-expression of human chaperones and furin proteases has shown promise, it is presently unclear how plant-specific differences in glycosylation impact the production of these proteins. In many cases it may be necessary to reproduce features of their native glycosylation to produce immunologically-relevant vaccines, given that glycosylation is central to the folding and immunogenicity of these antigens,. Building on previous work, we transiently expressed model glycoproteins from HIV and Marburg virus in Nicotiana benthamiana and mammalian cells. The proteins were purified and their site-specific glycosylation was determined by mass-spectrometry. Both glycoproteins yielded increased amounts of protein aggregates when produced in plants compared to the equivalent mammalian cell-derived proteins. The glycosylation profiles of the plant-produced glycoproteins were distinct from the mammalian cell produced proteins: they displayed lower levels of glycan occupancy, reduced complex glycans and large amounts of paucimannosidic structures. The elucidation of the site-specific glycosylation of viral glycoproteins produced in N. benthamiana is an important step towards producing heterologous viral glycoproteins in plants with authentic human-like glycosylation.